Fostering Competence in Medicines Development: The IFAPP Perspective - Dubois, Dominique J.; Jurczynska, Anna; Kerpel-Fronius, Sandor; Kesselring, Gustavo; Imamura, Kyoko; Nell, Gerfried; Silva, Honorio; Stonier, Peter (Frontiers in Pharmacology, 2016)
IFAPP is a nonprofit organization with the mission to promote Pharmaceutical Medicine & Medicines Development (PM&MD) by enhancing the competencies and maintaining high ethical standards of Pharmaceutical Physicians and other professionals involved in medicines development worldwide, leading to the availability and appropriate use of medicines for the benefit of patients and society.1 www.ifapp.org About 30 national professional associations related to PM&MD, involving 7000 professionals, are affiliated to IFAPP. Medicines development has traditionally been a challenging enterprise, with high risk, high investment and potentially high returns in the lengthy and complex process of identifying a new chemical entity as a candidate for development and possibly succeeding in bringing it as a pharmaceutical product to the market. However, the emergence of genomics, translational research, biomarkers and precision medicine pose challenges going forward involving allocation of resources, price, market access and cost-effectiveness as opposed to the traditional concepts of “efficacy” and “safety”. Education and Continuing Professional Development (CPD) are a major focus of IFAPP. The International Conference on Pharmaceutical Medicine (ICPM) is the largest event for our organization; ICPM is aimed to provide the state of the art in key areas for our discipline and profession. The paper is a reflection on the role of competency-based education and training for Pharmaceutical Physicians and medicines development scientists, as was discussed during the recent ICPM 2016 held in Sao Paulo, with the support of the Brazilian Association of Pharmaceutical Medicine and gathered around 200 representatives from the pharmaceutical, clinical research and regulatory arenas worldwide. http://www.icpm2016.com/en/programacao/programa;